Cervical intraepithelial neoplasia in women with transformation zone type 3: cervical biopsy versus large loop excision. (26th May 2022) - Gustafson, Line Winther; Hammer, Anne; Bennetsen, Mary Holten; Kristensen, Christina Blach; Majeed, Huda; Petersen, Lone Kjeld; Andersen, Berit; Bor, Pinar
Abstract: Objective: To compare the proportion of cervical intraepithelial neoplasia grade 2 or higher (CIN2+) in cervical biopsies with that in large loop excision of the transformation zone (LLETZ) specimens in women aged ≥45 years with transformation zone type 3 (TZ3). Design: Multicentre cross‐sectional study. Setting: Three colposcopy clinics in the Central Denmark Region. Population: Women aged ≥45 years referred to colposcopy as a result of a positive human papillomavirus (HPV) test and/or abnormal cytology and with TZ3 at colposcopy. Methods: Women had multiple biopsies taken and an LLETZ was performed. Main outcome measures: Histologically confirmed CIN2+ in biopsies compared with that in LLETZ specimens. Results: Of 166 eligible women at colposcopy, 102 women with paired data from biopsies and LLETZ specimens were included for final analysis. The median age was 67.7 years (IQR 62.6–70.4 years), and most were postmenopausal (94.1%) and had undergone HPV‐based screening (81.3%). The CIN2+ detection rate was significantly higher in LLETZ specimens than in biopsies (32.4% vs 14.7%, difference 17.7%, 95% CI 6.3–29.0%), resulting in more than half of CIN2+ cases being missed in biopsies (54.5%, 95% CI 36.4–71.9%). The overall agreement between biopsies and LLETZ was 82.4% (95% CI 73.6–89.2%). Conclusions: CIN2+ detection is underestimated in women aged ≥45 years with TZ3 if detection relies on the results of biopsies alone. To reduce the risk of underdiagnosis and overtreatment, future studies should explore the use of new biomarkers for risk stratification to improve discrimination between women at increased risk of CIN2+ who need to undergo LLETZ and women who may undergo follow‐up. Abstract : Linked article: This article is commented on by Sarah Feldman, pp. 2141 in this issue. To view this mini commentary visit https://doi.org/10.1111/1471‐0528.17260